Characterisation and pathogenicity of Fusarium species associated with yellowing disease in black pepper (Piper nigrum L.) - Shun, Hui Cheong; Kundat, Franklin Ragai; Mui, Yun Wong; Yee, Min Kwan (Universiti Kebangsaan Malaysia, 2022)
Yellowing disease has become one of the main threats to black pepper (Piper nigrum L.) production. This study was conducted to isolate and characterize Fusarium species associated with yellowing disease based on morphological and molecular characteristics, and to evaluate their pathogenicity on black pepper. Fungal isolates were recovered from symptomatic black pepper plants located in major growing areas in Sarawak. Based on morphological characteristics, a total of 73 Fusarium isolates were identified. Genomic DNA sequence analysis of nuclear ribosomal DNA internal transcribed spacer (ITS) and translation elongation factor-1 alpha (EF-1α) had confirmed the identity of the Fusarium isolates. The four identified Fusarium species were F. solani (90.4%), F. oxysporum (5.5%), F. concentricum (2.7%), and F. mangiferae (1.4%). Based on morphological characterisation, F. solani isolates were grouped into two distinct morphotypes, morphotype I and II. Phylogenetic analysis of F. solani has shown a high level of intraspecific variation among the isolates. The two major clades formed were found to correspond to the morphotype grouping. Pathogenicity test showed that all four Fusarium species are pathogenic to black pepper based on disease incidence and severity. This study provides new insights into the Fusarium species associated with yellowing disease in black pepper, and highlights the high genetic variability among the Fusarium isolates. This result calls for a critical revision of the current strategies in disease management, and resistance breeding programs in black pepper.